EXPOSING THE NATURE OF ARAB ISLAMIC REASONING AND ITS INFLUENCE TOWARD INDONESIA (Experiment of the Approach of M. Abed al-Jabiri’s Post Structuralism) - Mohamad Anas (Analisa: Journal of Social Science and Religion, 2019)
The post structuralism approach is no longer a conventional approach. The emergence of this new approach was not only to respond to structuralism, but also to answer the bluntness of the old approach which was barely able to read the very complex reality and to break down the so complicatedly cultural lines. What al-Jabiri practises in dismantling the nature of Arabic reasoning is his experiment in examining the Arab community reasoning. Interestingly, in practicing the post-structuralism approach, al-Jabiri does not only immediately practice it, but he reconstructs the post-structuralism approach by borrowing others for sharper analysis. It means that the post-structuralism approach is not the final approach. However, criticism and development are needed to achieve the establishment of theory.The foundation of the first theory of this research stems from Foucault's idea of archeology-genealogy of knowledge. The foundation of the next theory that the author takes from Foucault's thinking is about discourse. This research is entirely library research; therefore, the first step that researchers did is to collect primary data, especially data related to the focus of this research. The data analysis phase was carried out using the following methods: method of interpretation, analysis and historical.The results of the research indicate that the advantages of the post-structuralism approach are the methodological implications of very different readings and producing something else and new. The results are quite astonishing that al-Jabiri is able to examine the logic of Arabic construction and find the character of reasoning that had been thinkable and unthinkable. The post-structuralism approach is ultimately able to distinguish the nature of the Arab community's reasoning which can be distinguished into forming and formed reasoning.